Responsivitas Masyarakat Terhadap Manajemen Pelayanan Perpajakan Dalam Pembuatan Nomor Pokok Wajib Pajak (NPWP) Di Kantor Pelayanan Pajak (KPP) Pratama Sorong - Sardju, Arimbi; Akmal, Samsul; Hidayat, Rahmat Al (Jurnal Adminitrasi Bisnis Nusantara, 2024)
This research aims to determine the public's response in measuring the management of Taxpayer Identification Number services provided by the Pratama Sorong Tax Service Office (KPP). The research method uses a quantitative descriptive approach. The number of respondents involved was 100 people. The results of the research show that the KPP Pratama service management indicator that gets the highest score from community responsiveness in making NPWPs is the “Reliability” factor, with an average score of 9.18 and is at the "Very Good" level, followed by the other two factors which are also at the "Very Good" level. Those are the “Responsiveness” with a mean score of 8.83, and for and the Tangible of 8.73. Meanwhile, the other two factors are at the "Good" level, indicated by a mean score of 6.79 for the Assurance factor and 6.72 for the Emphaty factor.